Droughts Over Amazonia in 2005, 2010, and 2015: A Cloud Cover Perspective - Jimenez, Juan C.; Libonati, Renata; Peres, Leonardo F. (Frontiers in Earth Science, 2018)
Amazon forests experienced recent severe droughts in an anomalous short period induced by different mechanisms and had different length periods and spatial patterns. Droughts of 2005 and 2010 were attributed to anomalous sea surface temperature over the Tropical Atlantic during the dry season, but the 2010 drought was more severe and remained for a longer period because it was also induced in late 2009 by a moderate to strong El Niño (EN). Drought in 2015 led to unprecedented warming and extreme soil moisture deficits over some regions, and it was attributed to a very strong EN. Several studies analyzed these drought events regarding different climatic factors such as anomalies in sea surface temperature, vegetation, temperature, precipitation, soil moisture deficits, solar radiation, etc. However, we have not identified a complete analysis of cloud cover (CC) over Amazonia during these drought events in the context of long-term trends and past strong EN events. This brief report aims to present a preliminary analysis of anomalies in CC over Amazon using reanalysis data with a focus on the last recent drought events into a long-term context. Results show a significant decreasing trend for total CC over Southern Amazonia during the dry season, in contrast to the increasing trend found over Northern Amazonia during this season and the widespread increasing trend during the wet season. CC anomalies are also indicative of the different West-East and North-South patterns linked to EN events or drought episodes driven by tropical Atlantic warm anomalies.